American women pilots of World War II - Donnelly, Karen J. (New York The Rosen Publishing Group, INC, 2004)
Profiles American women who served as pilots during World War II, and describes their struggles to prove their value both in war time and after returning home.
Nancy Harkness Love -- Jacqueline Cochran: the beginnings -- Jacqueline Cochran: the WASP -- Evelyn Sharp -- Dorothy Swain Lewis -- Ann Baugartner Carl -- The flight home.
Includes bibliography references and Index
Keywords: Air pilots, Military -- United States -- Biography -- Juvenile literature; Women air pilots -- United States -- Biography -- Juvenile literature; World War -- Aerial operations, American -- Juvenile literature -- 1939-1945; United States -- Biography -- Juvenile literature; Women's rights -- History; World War -- Participation, Female. -- 1939-1945